Lactate metabolism during maximal work - Davies, Kelvin (My University, 1977)
The metabolism of lactate was studied in a group of male varsity track athletes (Ne17) aged 18-22, during a multi-stage treadmill test to mac. VO2. Two subgroups of the total group, consisting of sprinters (N=9) and distance runners (NP~) were examined for differences in lactatemetabolism. Respiratory gas exchange was measured at 30-sec. intervals and L-lactate concentration was determined from venous blood collected at 2-min. intervals. The relationship between venous lactate concentration and h2 for the total group was curvilinear, eta = -87,F (10,160) = 10.424, gC.01. The relationship between venous lactate concentration and b2 for sprinters, eta P .901,F (10, 80) = 7.396, g<.01, and for distance runners, eta = ,869,F (10, 80) = 5.402, P<.01, was found to be different, t (14) = 2.213, P<.01. The amplitude and direction of the lactate:VO2 curves for sprinters and distance runners were shown to be different by curvilinear regression. From differences between subgroups, the hypothesis that aerobic catabolism in distance runners continues to operate at a higher percentage of man. VO2 than in sprinters was constructed.
Keywords: Exercise - Physiological aspects; Energy metabolism